High-fat diet accelerate hepatic fatty acids synthesis in offspring male rats induced by perinatal exposure to nonylphenol - Hongyu Zhang; Chengguang Song; Rong Yan; Hongbo Cai; Yi Zhou; Xiaoyu Ke (BMC, 2021)
Abstract Background Low dose of NP exposure can alter adipose tissue formation, and the intake of high-fat diet (HFD) can also lead to the fatty liver disease. We investigated the combined effect of NP and HFD on the first offspring of rats, and whether this effect can be passed to the next generation and the possible mechanisms involved. Methods Pregnant rats had access to be treated with 5 μg/kg/day NP and normal diet. The first generation rats were given normal diet and HFD on postnatal day 21, respectively. Then the second generation rats started to only receive normal diet without NP or HFD. Body weight, organ coefficient of liver tissues, lipid profile, biochemical indexes and the expression of genes involved in lipid metabolism, as well as liver histopathology were investigated in male offspring of rats. Results NP and HFD interaction had significant effect on the birth weight, body weight and liver tissue organ coefficient of first generation male rats. And HFD aggravated abnormal lipid metabolism, even abnormal liver function and liver histopathological damage of first generation male rats produced by the NP. And this effect can be passed on to the second generation rats. HFD also accelerated the mRNA level of fatty acid synthesis genes such as Lpl, Fas, Srebp-1 and Ppar-γ of first generation rats induced by perinatal exposure to NP, even passed on to the second generation of male rats. NP and HFD resulted in synergistical decrease of the protein expression level of ERα in liver tissue in F2 male rats. Conclusion HFD and NP synergistically accelerated synthesis of fatty acids in liver of male offspring rats through reducing the expression of ERα, which induced abnormal lipid metabolism, abnormal liver function and hepatic steatosis. Moreover, all of these damage passed on to the next generation rats.